Advanced Cervical Squamous Cell Carcinoma with Skin Metastasis - Chia-Hui Chen; Kuan-Chong Chao; Peng-Hui Wang (Elsevier, 2007)
Objective: Although cervical cancer is a very common gynecologic malignancy, skin metastasis presenting as an initial sign of recurrent or persistent disease is extremely rare. Case Report: A 72-year-old woman was diagnosed with squamous cell carcinoma of the cervix (FIGO stage, IIB), which was treated with concurrent chemoradiation. After treatment, she was followed up regularly, without evidence of disease. One year later, many erythematous lesions were noted on the extremities, trunk, and scalp. Some of skin lesions grew rapidly. Excision biopsy was performed and showed metastatic carcinoma, favoring a squamous cell type. The patient then underwent a series of imaging examinations, including magnetic resonance imaging of the pelvis and computed tomography of the chest, and a whole body bone scan showed disseminated diseases involving the lung and bone. Palliative chemotherapy was prescribed, and the skin lesions responded relatively well, but disease involving the vital organs still progressed during treatment. The patient died of the disease 6 months after the appearance of the skin lesion. Conclusion: This report supports the concept that skin metastasis is a late manifestation and an ominous sign for cervical cancer patients, and also indicates the uncontrolled or widespread metastasis of the disease.